Symbolic aesthetics in steel structural systems - Usama Abdul-Mun'em Khuraibet (Journal of Engineering, 2015)
The aesthetic expression and its orders are important for steel structures forming. Steel structures are a compilation of structural elements, where its shapes have standard dimensions and pre-fabricated. As the steel construction systems not only aim to achieve the functional requirements for users, but must also have the symbolic aesthetics which provides visually and cognitive expression for viewers. In this sense the research interested in expressional aesthetics in these systems and highlights the importance of attention as structural items. Therefore the visual items which related with steel structures contain some of the most powerful forms of modern architecture, steel structures with a glass cladding, agility and accuracy in manufacture of structural elements as visual items, structural interest in the forms of spaces which have long span systems or in high buildings are different forms of expression and influence. So the research focuses on the study of those expressive patterns related with the steel construction properties, including the advantages of these systems at the level of strength and firmness, flexibility and economy as well as aesthetic and expression. Accordingly, the research problem concentrated on educational shortage in the study of the structural steel system aspects concerning constructional characteristic, expressive and aesthetic features, and how to deal with them as a language bearing the symbols and meanings which have clear structural style, because it the best ways to make those systems as communication means with users, by premise that the use of expressional symbol in steel construction increases the aesthetic value. Therefore the research aims to reveal the most structural and expressive patterns by analysis the expressional means and steel structural aesthetics.